A new approach to design multi-loop control systems with multiple controllers - Gambier, Adrián; Wellenreuther, Andrea; Badreddin, Essameddin (45th IEEE Conference on Decision and Control, 2006, 2007)
In this contribution, a new method to design multi-loop control systems with several controllers is proposed. Controllers are assumed to be players of a cooperative dynamic game, whose solution is obtained by multi-objective optimization (MOO). The MOO problem is solved by applying a genetic algorithm and the final solution is found from an optimal Pareto set. As illustrative example, the control system design of a reverse osmosis desalination plant is used. Simulation results are satisfactory and show that in many cases, as for example this desalination plant, multi-loop control with several controllers, which have been obtained by join multi-objective optimization, perform as good as more complex controllers but with less implementation effort.